Evaluasi Kesesuaian Tambak Garam Ditinjau Dari Aspek Fisik Di Kecamatan Juwana Kabupaten Pati - Renaldi Bahri Tambunan; Hariyadi Hariyadi; Adi Santoso (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro, 2013)
Salt is one of the national strategic commodities in the field of marine. Effort to increase the quantity and quality of salt production has not been a priority for farmers in Juwana. It examined regarding evaluated the suitability of the physical land of salt embankment in Pati Juwana to approach some of the factors are soil permeability, climatology, soil type and topography of the form. The purpose of this research is to know and study the suitability of the salt level land embankment in district Juwana, Pati. This research using several physical analysis of the permeability of soil, land forms and types, climatic conditions and scoring physical suitable of salt embankment. The results of this study indicate that the suitability of physical salt embankment in Juwana, Pati has a physical suitability class is very suitable (S1) to produce a national salt.